2015
DOI: 10.1080/09168451.2015.1015956
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of cytochrome c′ from mesophilic Shewanella amazonensis

Abstract: Cytochrome c' (SACP) from mesophilic Shewanella amazonensis, growing optimally at 37 °C, was thermally more stable than cytochrome c' (AVCP) from mesophilic Allochromatium vinosum, growing optimally at 25 °C. In contrast, SACP was less stable than cytochrome c' (PHCP) from thermophilic Hydrogenophilus thermoluteolus, growing optimally at 52 °C. Although only 28% of the SACP amino acid sequence was identical to those of AVCP and PHCP, the latter two being 55% identical, the overall main chain structures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Previously, we found that cytochrome c ′ (PHCP) from thermophilic Hydrogenophilus thermoluteolus (formally called Pseudmonas hydrogenothermophila ) growing optimally at 52°C showed high thermal stability compared with cytochrome c ′ (AVCP) from mesophilic Allochromatium vinosum growing optimally at 25–30°C . Cytochrome c ′ from another mesophilic bacterium, Shewanella amazonensis , growing optimally at 37°C exhibited thermal stability that was intermediate between those of AVCP and PHCP . The thermal stability of these three proteins positively correlates with the growth temperatures of the source bacteria, thus a comparative study on protein stability can be carried out using these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that cytochrome c ′ (PHCP) from thermophilic Hydrogenophilus thermoluteolus (formally called Pseudmonas hydrogenothermophila ) growing optimally at 52°C showed high thermal stability compared with cytochrome c ′ (AVCP) from mesophilic Allochromatium vinosum growing optimally at 25–30°C . Cytochrome c ′ from another mesophilic bacterium, Shewanella amazonensis , growing optimally at 37°C exhibited thermal stability that was intermediate between those of AVCP and PHCP . The thermal stability of these three proteins positively correlates with the growth temperatures of the source bacteria, thus a comparative study on protein stability can be carried out using these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The wide distribution of Shewanella species also makes them suitable bacteria for investigating not only the enzymatic reactions that drive biogeochemical cycles (Falkowski et al 2008), but also the protein stability mechanism as to such various environments. In this context, we have carried out protein thermal stability studies using cytochromes c isolated from a variety of Shewanella species (Ogawa et al 2007;Takenaka et al 2010;Masanari et al 2011;Kato et al 2015). Recently, we found a positive correlation between the optimal growth pressures of four Shewanella species and the stabilities of their highly homologous cytochromes c 5 (Masanari et al 2014;Masanari et al 2016).…”
mentioning
confidence: 99%